2013
DOI: 10.1038/srep03208
|View full text |Cite
|
Sign up to set email alerts
|

Activated boron nitride as an effective adsorbent for metal ions and organic pollutants

Abstract: Novel activated boron nitride (BN) as an effective adsorbent for pollutants in water and air has been reported in the present work. The activated BN was synthesized by a simple structure-directed method that enabled us to control the surface area, pore volume, crystal defects and surface groups. The obtained BN exhibits an super high surface area of 2078 m2/g, a large pore volume of 1.66 cm3/g and a special multimodal microporous/mesoporous structure located at ~ 1.3, ~ 2.7, and ~ 3.9 nm, respectively. More im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(172 citation statements)
references
References 50 publications
2
170
0
Order By: Relevance
“…Consequently, while idealised basal surfaces should contain hexagons composed of boron and nitrogen alone, it is likely that the edges of hBN sheets will contain species such as hydroxyl groups. Indeed, examination of the as-supplied hBN power used here by Fourier-transform infrared spectroscopy (FTIR) revealed the presence of weak absorption bands centred at 3131 and 3420 cm -1 , which can be associated the stretching of O-H and N-H bonds, as reported elsewhere [27][28][29][30][31]. However, if the true structure were to differ markedly from the ideal, then the presence of many polar surface groups would be expected to lead to hydrogen bonds with any labile polar species present in the system, most notably, water.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, while idealised basal surfaces should contain hexagons composed of boron and nitrogen alone, it is likely that the edges of hBN sheets will contain species such as hydroxyl groups. Indeed, examination of the as-supplied hBN power used here by Fourier-transform infrared spectroscopy (FTIR) revealed the presence of weak absorption bands centred at 3131 and 3420 cm -1 , which can be associated the stretching of O-H and N-H bonds, as reported elsewhere [27][28][29][30][31]. However, if the true structure were to differ markedly from the ideal, then the presence of many polar surface groups would be expected to lead to hydrogen bonds with any labile polar species present in the system, most notably, water.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, surface/interface engineering with metal ions are encouraged since BCN-based materials feature the "lop-sided" densities characteristic of ionic B-N bonding, and the polyelectronic nitride can transfer more electron density to metal ions [36,37]. They are thus effective for the adsorption of metal ions, chemically, as highlighted here by surface engineering via cobalt ions (Scheme 1).…”
Section: Science China Materialsmentioning
confidence: 99%
“…Some examples of templates employed include mesoporous silica, carbonaceous materials and zeolites [25][26][27]. Various organic compounds have also been mixed with boron and nitrogen precursors and used as structure-directing agents to produce porous BN, such as for instance cetyl-trimethylammonium bromide [28], or the triblock copolymer (P123) [12].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Recent studies have reported the use of porous BN for gas phase and liquid phase adsorption. The focus has mostly been on CO 2 capture [4][5][6], H 2 storage [7][8][9][10], pollutants removal from air [11,12], water pollutants removal [7,[12][13][14][15][16][17][18][19][20][21][22] and oil adsorption [15,21,22]. For instance, recent work by Nag et al [5] reported the synthesis of boron nitride with a CO 2 adsorption capacity of up to 32 wt.…”
Section: Introductionmentioning
confidence: 99%